2014
DOI: 10.7314/apjcp.2014.15.9.3981
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma Lucidum Polysaccharides Target a Fas/Caspase Dependent Pathway to Induce Apoptosis in Human Colon Cancer Cells

Abstract: Ganoderma lucidum polysaccharides (GLP) extracted from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The extracellular death domain reacts with the FADD to form the death induced signal complex, and then activates the caspase-8 as well as the following cascade reaction, thus inducing the apoptosis of cells in presence of Fas protein [23]. Wang et al [24] discussed the HepG-2 proliferation inhibition of Litchi seeds extract and found that the extract L2.3 could stimulate the activity of caspase-8, caspase-3 and caspase-9 and induce the expression of Fas protein (CH3, Figure 1).…”
Section: Regulating the Expression Of Fas Proteinmentioning
confidence: 99%
“…The extracellular death domain reacts with the FADD to form the death induced signal complex, and then activates the caspase-8 as well as the following cascade reaction, thus inducing the apoptosis of cells in presence of Fas protein [23]. Wang et al [24] discussed the HepG-2 proliferation inhibition of Litchi seeds extract and found that the extract L2.3 could stimulate the activity of caspase-8, caspase-3 and caspase-9 and induce the expression of Fas protein (CH3, Figure 1).…”
Section: Regulating the Expression Of Fas Proteinmentioning
confidence: 99%
“…Recently, many extracts from Chinese medicine have begun to be used as a new strategy for cancer therapy; for example, Ganoderma lucidum polysaccharide and extracts from Aristolochia could induce apoptosis of human colon cancer cells. 6,7 Noticeably, various polyphenolic compounds found in food have been confirmed to have different pharmaceutical functions. 8,9 Previous studies showed that green tea polyphenols could inhibit the growth of breast, lung, and cervical adenocarcinomas by blocking the c-terminal polo-box domain of polo-like kinase 1 10 ; moreover, red wine polyphenol extracts are found to have superior antiproliferative activity in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is presented in all tissues of the body within the cytoplasm. Once the cells are damaged, LDH was then released into extracellular, the extent of cell damage can be detected by LDH activity [40]. The higher the LDH activity, the more serious the cell injured [41].…”
Section: Discussionmentioning
confidence: 99%